2018
DOI: 10.1016/j.cell.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Fragile X Syndrome Neurons by DNA Methylation Editing of the FMR1 Gene

Abstract: Fragile X syndrome (FXS), the most common genetic form of intellectual disability in males, is caused by silencing of the FMR1 gene associated with hypermethylation of the CGG expansion mutation in the 5' UTR of FMR1 in FXS patients. Here, we applied recently developed DNA methylation editing tools to reverse this hypermethylation event. Targeted demethylation of the CGG expansion by dCas9-Tet1/single guide RNA (sgRNA) switched the heterochromatin status of the upstream FMR1 promoter to an active chromatin sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
319
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(332 citation statements)
references
References 72 publications
12
319
0
1
Order By: Relevance
“…39,40 Repeat size mosaicism is characterized by the presence of cell populations with different CGG repeat sizes, most commonly one cell population with a full mutation and another with a premutation. Other combinations of full mutation, premutation, grey zone (45)(46)(47)(48)(49)(50)(51)(52)(53)(54), and normal CGG size have also been reported, and may not be as uncommon as previously thought. 17 Repeat size mosaicism is thought to arise, in most cases, from a full mutation conception, with subsequent contraction of the full mutation to a smaller size alleles in one or more cell lineages.…”
Section: Mosaicism and Fxsmentioning
confidence: 66%
See 2 more Smart Citations
“…39,40 Repeat size mosaicism is characterized by the presence of cell populations with different CGG repeat sizes, most commonly one cell population with a full mutation and another with a premutation. Other combinations of full mutation, premutation, grey zone (45)(46)(47)(48)(49)(50)(51)(52)(53)(54), and normal CGG size have also been reported, and may not be as uncommon as previously thought. 17 Repeat size mosaicism is thought to arise, in most cases, from a full mutation conception, with subsequent contraction of the full mutation to a smaller size alleles in one or more cell lineages.…”
Section: Mosaicism and Fxsmentioning
confidence: 66%
“…First, CRISPR/Cas9 gene editing has been used to excise the CGG repeat expansion in patient‐derived FXS‐induced pluripotent stem cells, with resultant demethylation of the FMR1 promoter and reactivation of FMRP production . More recently, the Cas9 system has been adapted to allow targeted editing of DNA methylation without altering the DNA sequence . Using this approach, studies in FXS‐induced pluripotent stem cells have demonstrated demethylation of both the FMR1 CGG expansion and the FREE1 region, with consequent de‐repression of FMR1 chromatin, restoration of FMRP expression, and the rescue of electrophysiological abnormalities in FXS neurons …”
Section: Epigenetic‐based Therapies For Fxsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a potential candidate for therapeutic application of epigenetic editing is fragile X syndrome, which is caused by a GGC expansion leading to the silencing of FMR1. Targeting the repeat by a dCas9-Tet fusion protein caused demethylation of the repeat, restoration of FMR1 expression and reversal of electrophysiological abnormalities in fragile X patient-derived neurons (Liu et al, 2018). Pooled epigenome editing screens can systematically analyze the functional consequences of modulating the activity of non-coding elements and interrogate the function of GWAS identified risk variants in regulatory elements on a genome scale (Fulco et al, 2016; Hilton et al, 2015; Thakore et al, 2015).…”
Section: Hpsc Models Of Complex Diseases - Functional Analysis Of Dismentioning
confidence: 99%
“…These transient hit-and-run approaches enabled persistent de novo DNA methylation on the targeted CpG islands by instructing self-sustaining repressive epigenetic states in a chromatin environment and resisting to transcriptional activation stimuli (Amabile et al 2016). In contrast, robust and transient DNA demethylation of the promoter to induce target gene expression was achieved using dCas9-TET1 (Liu et al 2016; Liu et al 2018b). TET1 is a methylcytosine dioxygenase that plays a key role in active DNA demethylation by converting 5-methylcytosines (5mCs) to 5-hydroxymethylcytosines (5hmCs) (Guo et al 2011).…”
Section: Crispr-based Epigenome Editing and Transcriptional Modulatiomentioning
confidence: 99%